Unprecedented disruption of lives due to COVID-19 pandemic on health of pregnant women - Ghosh, Shashwatee; Fuke, Rujuta; Harikanth, Disha R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: COVID-19 pandemic has caused havoc worldwide. The quarantine imposed in this country aimed at combating this deadly disease and also created awareness amongst the masses. Though there was a decrease in case load; unemployment and food scarcity crumbled the Indian economy. This caused a significant impact on the population especially among the pregnant women. Aim was to assess the effects of measures to control COVID-19 pandemic on the health of pregnant women. Methods: A cross sectional analytical study conducted in May 2020 among 343 pregnant women attending antenatal outpatient department (OPD) in Government Medical College, Nagpur. They were interviewed using a structured questionnaire. Results: The study showed that majority women were 25-29 years old and most of them had education of high school level with income under 10,000. Anger and fear were the most common untoward feelings perceived by these pregnant women during pandemic. Most of them had neutral opinion regarding the impact of lockdown on their routine lives. And almost all felt that India would fight the COVID-19 pandemic through lockdown. Majority women reduced their hospital visits during pandemic even-though there was no difficulty in transportation. Although maximum women found it easy to avail medicines in pharmacy there was tremendous food scarcity and decreased earning. Conclusions: The study stresses on the need to provide mental health awareness among pregnant women during pandemic and to tackle any social inequalities. It also encourages the government to undertake time bound policy evaluation.